PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE AMATCHUNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 003BANTAYAN BARU KECAMATAN BATU HAMPAR - Antosa, Zariul Antosa; Daud, Damanhuri Daud; ', Susiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem this research is the student achivement of IPS Fourth garders studies still low with an average value 62 and minimum completeness criteria ( KKM ) IPS is 70. Between students amounting to34 pepole only 11 students who achieve clasical KKM. This research is classroom action Research (CAR). Which aims to improve the student achievement of IPS sudies clas IV at SDN 003 BantayanBaru with implementation cooperative learning model make a match. Formulation of the problem : Is the implementation of cooferative learning model make a match can improve students achivement of IPS studies at SDN 003 BantayanBaru. Subjects were students Of SDN 003Bantayan Baru. Totalling 34 people who use the data source, the data collection intruments in this thesis present the result obtained each day before the action improved in base score cycle with the average being 62. In the first cycle improve in average of 70 and an improve second cycle with an average of 70,6. Activities of the teacher in the learning process at the cycle one 70,6 and 76,9 and in the second cycle improved. So the result in class IV SDN 003Bantayan Baru that the implementation of cooperatiff learning model make a match can Improved the student Achivement of IPS studies at fourth graders SDN 003 BantayanBaru. Keyword : cooperatiff learning model make a match can Improved the student Achivement of IPS studies at fourth graders SDN 003 BantayanBaru